2013
DOI: 10.3390/ijms141122042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cold Ischemia on Mitochondrial Function in Porcine Hearts and Blood Vessels

Abstract: The effects of cold storage using Custodiol® (Histidine-Tryptophan-Ketoglutarate, HTK) or isotonic saline solution on mitochondrial function in hearts (left and rights ventricles) and various blood vessels of pigs were investigated. Hearts, saphenous veins, internal-mammary-arteries and aortas of male landrace pigs were harvested and exposed to cold ischemia in either saline or Custodiol-HTK solution. Mitochondrial function was measured in situ in permeabilized fibers by high-resolution respirometry. Mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Our data are in general very comparable with the literature [42,43] with respect to the respiratory parameters of oxygen flux (expressed in wet weight (ww)). Similar to previous reports [29,44,45], we also showed that AMI decreased mitochondrial respiration in cardiac cells in different functional states, mainly those associated to ATP synthesis, with ultrastructural modifications in an acute lesion scenario. The feeding by electrons of the ETS in the necrotic phase was more affected through complex I (NADH: ubiquinone oxidoreductase) than that starting from the succinate dehydrogenase (complex II), although both were completely damaged in the fibrotic phase of the IZ (IZ still responded to succinate addition during the necrotic phase).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data are in general very comparable with the literature [42,43] with respect to the respiratory parameters of oxygen flux (expressed in wet weight (ww)). Similar to previous reports [29,44,45], we also showed that AMI decreased mitochondrial respiration in cardiac cells in different functional states, mainly those associated to ATP synthesis, with ultrastructural modifications in an acute lesion scenario. The feeding by electrons of the ETS in the necrotic phase was more affected through complex I (NADH: ubiquinone oxidoreductase) than that starting from the succinate dehydrogenase (complex II), although both were completely damaged in the fibrotic phase of the IZ (IZ still responded to succinate addition during the necrotic phase).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the accentuated increase in respiration after addition of cytochrome c (Figure 3(k)) at the acute phase in IZ-which reveals important damage in the internal mitochondrial membrane and cytochrome c release-could be considered a key and transient event determining the fate of the fibers towards cardiomyocyte death. The increase that doubles the accepted normal values around 15% [56] shows the trigger of the apoptotic cascade [45,57,58], which progressively culminates with late left ventricle dysfunction. The normalized values of cytochrome c found in IZ during fibrotic phase could be justified by the low response to most part of the reagents (Figure 3).…”
Section: Discussionmentioning
confidence: 81%
“…The most energy-consuming organ, the heart, containing the biggest mitochondrial content (30% of cell volume), is also most sensitive to IR injury compared with other, less energy-dependent organs [134]. Damage to mitochondrial respiratory chain complexes after ischemia (including also cold ischemia and organ preservation) alone is also significantly different and produces more pronounced injury after reperfusion.…”
Section: Mitochondrial Energy Metabolism In Cardiac Ir Injurymentioning
confidence: 99%
“…They also demonstrated ultrastructural changes of mitochondria in TEM analysis (mitochondria swollen, cristae impairment, and structural anomalies). Using the permeabilized muscle fibers technique, Wiedemann and colleagues 26 showed that cold ischemia storage in saline solution was associated with a decrease of mitochondrial respiratory capacities of complex I (after glutamate þ malate-supported respiration) and complex II (succinate þ rotenone-supported respiration).…”
Section: Mechanistic Hypothesismentioning
confidence: 99%